Application of Web-Based Plant Disease Diagnosis (Case Study: Farmers in Pagaralam City) - Aminah, Siti (Sekolah Tinggi Teknologi Adisutjipto, 2019)
The purpose of this research is an expert system to diagnose diseases on web-based rice plants that can make it easy for farmers to get knowledge about rice diseases and how to handle them. Pagar Alam is a mountainous area, the majority of which are farmers. Data obtained from the Department of Agriculture of the City of Pagaralam stated that there were several types of rice planted in the Pagar Alam area, including Situbagendit, IR 64, Padi TS, Inpara 1-8, but most Cierang rice species were planted in the Pagar Alam area. It is not impossible for farmers to experience a yield setback, even to the point of crop failure due to lack of knowledge about the diseases that attack their rice plants. The system development method used is Rapid Application Development (RAD). Therefore, the researchers made an application of a Web-Based Expert System for Rice Disease Diagnosis to Improve the Welfare of Farmers in Pagar Alam City. With the application of an expert system, it can provide information on plant disease pests and can diagnose the symptoms of plant diseases, especially rice plants, as well as provide a solution to overcome them, which can later be used to reduce or reduce the risk of crop damage. The results of the study are in the form of an expert system for diagnosing diseases in web-based rice plants